Thai and Khmer Traditional Mahori: Comparison of Musical Cultural Characteristics - Kingkaew, Sippavich (Journal of the Faculty of Arts, Silpakorn University, 2020)
This article aims to comparatively examine the characteristics of Thai and Khmer Mahori. Although the Thai Mahori, which is a string-dominated classical ensemble, was originally emerged in the Ayutthaya period after Thais adopted the Khmer Mahori’s tradition, the development of the Thai and Khmer Mahori throughout their histories has brought them unique characteristics. Based upon these characteristics, the ﬁndings can be categorized into two groups of common and different characteristics of the two nations’ classical ensembles. The study showed that the common characteristics of the Thai and Khmer Mahori are (1) the ensembles’ similar selection of musical instruments and their instrumentation and (2) their similar tradition in naming songs which always suggest their ethnic musical expressions through the ﬁrst words of the songs. Regarding the differences in the culture in music of the Thai and Khmer Mahori, two aspects were evidenced. The ﬁrst difference is that the origin of the Thai Mahori’s music and documentation has been evidenced since the Ayutthaya period, but this was not the case for the Khmer Mahori. Second, the purposes of the two nations’ classical ensembles are different. In the past, the Thai Mahori was called for participatory to the court ceremonies and entertaining occasions while it is performed only in entertaining occasions at present. Compared with the Thai Mahori, the Khmer Mahori has been performed solely for entertaining purposes since the old days. The only change in it is that, in order to make it more accessible to people, the Khmer Mahori’s instrumentation has been adjusted to serve more average audience.